Asuhan Keperawatan Jiwa Pada Tn. R dengan Masalah Utama Gangguan Sensori Persepsi: Halusinasi Pendengaran Akibat Skizofrenia Tak Terinci: Studi Kasus di Ruang Hudowo RSJD dr. Amino Gondohutomo Provinsi Jawa Tengah - Ahmad Akhyarudin Aziz; Titi Sri Suyanti; Tati Karyawati (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Mental health is an important aspect that supports quality of life, including a state of well-being related to happiness, satisfaction, achievement, optimism, and dynamic hope according to life situations (Fitri, 2025; Herlina et al., 2024). Schizophrenia is a severe mental disorder characterized by an inability to communicate, impaired perception of reality (illusions and hallucinations), and loss of self-confidence, included in the category of psychosis (Mardiana et al., 2024). The purpose of writing this scientific paper is to find out and implement psychiatric nursing care for Mr. R, with the main problem of sensory perception disorders: auditory hallucinations due to schizophrenia that are not detailed in the Hudowol Room of Dr. Amino Gondohutomo Mental Hospital, Central Java Province. The method used is a descriptive approach with a case study. The case review results showed that the client heard male and female voices saying negative things and often talked to himself. The problem tree identified sensory perception disorders: auditory hallucinations as the core problem, accompanied by self-care deficits, social isolation, and the risk of violent behavior. Interventions are designed based on implementation strategy guidelines for clients and families, implemented, and evaluated as documented evidence